Nano-zinc oxide (nZnO) targets the AMPK-ULK1 pathway to promote bone regeneration - Xiu Chen; Zhenkun Weng; Hongchao Zhang; Jian Jiao; Jingjia Liang; Jin Xu; Dongmei Wang; Qian Liu; Qing Yan; Aihua Gu (Stem Cell Research & Therapy)
Abstract Background Nano-zinc oxide (nZnO) has attracted significant attention in bone tissue engineering due to its antibacterial properties, anti-inflammatory effects, biocompatibility, and chemical stability. Although numerous studies have demonstrated the enhancement of osteogenic differentiation by nZnO-modified tissue engineering materials, the underlying mechanisms remain poorly characterized. Methods This study aimed to identify the molecular mechanisms how nZnO promoted osteogenic differentiation and bone regeneration using transcriptome analysis, drug intervention, and shRNA knockdown techniques, etc. First, the study evaluated the in vivo effects of gelatin methacryloyl (GelMA) containing nZnO on bone regeneration using a mouse calvarial defect model. The impact of nZnO exposure on the osteogenic differentiation of mesenchymal stem cells (MSCs) was then assessed. The combined treatment of nZnO and MSCs in GelMA for bone regeneration was assessed in the mouse calvarial defect model thereafter. Results nZnO induced osteoblastic differentiation to promote bone regeneration. nZnO activated the AMP-dependent protein kinase (AMPK)-ULK1 signals to stimulate autophagosomes formation and facilitate autophagy flow, which was the essential pathway to induce osteogenic differentiation. The combined treatment of MSCs and nZnO significantly enhanced bone regeneration in calvarial defect mice. Conversely, AMPK inhibitor Compound C (C.C) reversed the effects on autophagy flow and osteogenic potentiality induced by nZnO. Conclusions These results highlight that nZnO can regulate bone regeneration by activating autophagy through the AMPK/ULK1 signaling pathway, which may provide a novel therapeutic strategy for addressing bone defects using nZnO.